Pengaruh Green Product Innovation Dan Green Process Innovation Terhadap Nilai Perusahaan - Fitriana Noer Hidayah; Mentiana Sibarani (JAF (Journal of Accounting and Finance), 2023)
The current deteriorating condition of the earth and the environment has become one of the main assessment bases for stakeholders in making decisions. A company is expected to have a role and participation in environmental improvement. The purpose of this study was to determine the effect of green innovation on firm value in companies listed on the Indonesia Stock Exchange and the best listed in implementing green business based on Indonesia Green Companies SWA Magazine. The research data was obtained from sample financial statements contained on the Indonesia Stock Exchange for the 2017- 2020 period from the company's website or the Indonesia Stock Exchange website. The sample used is companies listed in Indonesia Green Companies and listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The sampling technique used is purposive sampling. Hypothesis testing in this study using multiple linear regression analysis method. The results of this study indicate that green product innovation and green process innovation have a simultaneous effect on firm value, green product innovation has a significant effect on firm value, green process innovation has no significant effect on firm value. Keywords: Green Innovation, Green Product Innovation, Green Process Innovation, Company Value